Tunable Cloaking of Mexican-hat Confined States in Bilayer Silicene - Ho, Le Bin; Tran, Lan Nguyen (Communications in Physics, 2019)
We present the ballistic quantum transport of a p-n-p bilayer silicene junction in the presence of spin-orbit coupling and electric field using a four-band model in combination with the transfer-matrix approach. A Mexican-hat shape of low-energy spectrum is observed similarly to bilayer graphene under an interalayer bias. We show that while bilayer silicene shares some physics with bilayer graphene, it has many intriguing phenomena that have not been reported for the latter. First, the confined state producing a significantly non-zero transmission in Mexican hat. Second, the cloaking of the Mexican-hat confined state is found. Third, we observe that the Mexican-hat cloaking results in a strong oscillation of conductance when the incident energy is below the potential height. Finally, unlike monolayer silicene, the conductance at large interlayer distances increases with the rise of electric field when the incident energy is above the potential height.